Preventive dental care utilization for children with special healthcare needs including the COVID-19 pandemic, national survey of children's health, 2020 - R. Constance Wiener (Public Library of Science (PLoS), 2023)
It is important to determine access to preventive care among vulnerable populations. The purpose of this research is to compare preventive dental utilization between children with special healthcare needs (CSHCN) and children without special healthcare needs (CWSHCN) using National Survey of Children's Health, 2020 (NSCH, 2020) data. A cross-sectional study design was used in this secondary data analysis of data from June 2020 to January 2021, NSCH, 2020, a publicly available data set with demographic and healthcare information. Parents/guardians responded to validated questions including one asking them to recall preventive dental services received during the previous year (June 2019 to January 2021). This was a critical time of transition from normal, pre-pandemic activities (June 2019 to March 2020) to the pandemic period (March 2020 to January 2021) with restrictions and no available vaccinations for children. Data analyses for the NSCH, 2020 data included frequency determinations, Chi Square analyses by preventive dental visit, and logistic regression analyses. There were 40,140 children in the sample, and 20.6% were CSHCN. Overall, 75.0% of children received a dental preventive visit. This study had an interaction of CSHCN status and medical visits within the previous year in which having had a medical visit was associated with CSHCN status also having a dental visit; while the CSHCN who did not have a medical visit were less likely to have a dental visit in unadjusted analysis. However, the pattern for CSHCN and the medical visit reversed in adjusted analysis. In adjusted analysis, CWSHCN and a medical visit were the most likely to also have a dental visit during this period. Many factors influenced access to preventive dental care in the months leading up to and including the COVID-19 pandemic. CSHCN with or without a medical visit were less likely to have preventive dental care than CWSHCN with a medical visit in logistic regression analysis adjusted for sex, race/ethnicity, age, smoking in the household, medical visits within the year, insurance coverage, and highest level of education in the household.